Non-Invasive Assessment of Vascular Damage Through Pulse Wave Velocity and Superb Microvascular Imaging in Pre-Dialysis Patients - Julia Martín-Vírgala; Beatriz Martín-Carro; Sara Fernández-Villabrille; Belinda Fernández-Mariño; Elena Astudillo-Cortés; Minerva Rodríguez-García; Carmen Díaz-Corte; José Luis Fernández-Martín; Carlos Gómez-Alonso; Adriana S. Dusso; Cristina Alonso-Montes; Manuel Naves-Díaz; et al. (Biomedicines)
Background/Objectives: Cardiovascular disease is the main cause of morbidity and mortality in Chronic Kidney Disease (CKD), so it is of great importance to find simple and non-invasive tools to detect vascular damage in pre-dialysis CKD patients. This study aimed to assess the applicability of non-invasive techniques to evaluate vascular damage in stages CKD-2 to CKD-5 and its progression after an 18-month follow-up using (A) carotid–femoral pulse wave velocity (PWV) to assess aortic stiffness and (B) Superb Microvascular Imaging (SMI) ultrasound to assess adventitial neovascularization compared with other traditional techniques to evaluate vascular damage, such as carotid intima–media thickness and Kauppila index. Methods: The study involved 43 CKD patients in stages CKD-2 to CKD-5 and a group of 38 sex- and age-matched controls, studied at baseline and at an 18-month follow-up. Age, sex, body mass index, arterial pressure, pharmacological treatments, and blood and urinary parameters were collected. Aortic stiffness was determined by carotid–femoral PWV and abdominal aortic calcification was assessed in lateral lumbar X-rays and quantified by the Kauppila index. Carotid intima–media thickness (cIMT), the number of carotid plaques, and adventitial neovascularization were evaluated by SMI. Results: Vascular impairment was mostly detected in CKD-4 and CKD-5 stages, with increased aortic stiffness measured by PWV and increased carotid plaques and adventitial neovascularization measured by SMI ultrasound. Furthermore, CKD-5 patients showed greater abdominal aortic calcification. Interestingly, CKD patients displayed a negative correlation between serum soluble Klotho (sKlotho) and cIMT. Finally, CKD patients showed no progression of vascular impairment after the 18-month follow-up, with the exception of carotid plaques. Conclusions: Performing non-invasive PWV and SMI ultrasound might be useful to evaluate vascular damage in CKD before entering dialysis, possibly helping to prevent cardiovascular events, although future studies should clarify the use of these techniques in clinical practice.